AN ANALYSIS OF DIRECTIVE SPEECH ACT FOUND IN “KOI MIL GAYA” MOVIE - Tira Nur Fitria (Journal of Pragmatics Research, 2019)
The aim of this research is to find out the type of directive speech acts and to find out which directive speech acts most frequently used in “Koi Mil Gaya” movie. The research is conducted by using a qualitative approach. This research describes the phenomenon, the data, the situation, as it is really found. The technique of data collection in this research is a documentary study. From the result of this study, the writer finds that there are 246 utterances of directive speech act produced by the characters in the movie as 196 data. The form of the directive act can be found in utterances which contain words, phrase, clause, and sentences. From the analysis shows that in “Koi Mil Gaya” movie shows a directive speech act which contains three aspects, they are command, request, and suggestion. First, in command, there are 165 data (utterances) or 84.18 %. Second, in suggestion, there are 20 data/utterances or 10.20 %. Third, in a request there are 11 data//utterances or 5.61 %. While the most dominant type of directive speech act is in command.Keywords: Speech Act, Directive, Movie